A “Double Delta”-Shaped Suturing Technique for Moderate Crescent-Shaped Rotator Cuff Tear - Jiahao Zhang, M.D.; Yu Mei, M.D.; Fengyuan Zhao, M.D.; Hui Yan, Ph.D., M.D. (Arthroscopy Techniques)
The crescent-shaped tear is one of the most common rotator cuff tear patterns that can be repaired directly to bone with minimal tension. For the moderate crescent-shaped tear, a single-row technique may not be enough to maximize the contact area of footprint, and the double-row technique with 2 medial anchors may be crowded in the restricted medial space of footprint. To offer a better solution, we introduce a suitable “double delta”-shaped suturing technique with 3 suture anchors, 4 suture sites, and 6 knots.